INFORMATION TECHNOLOGY OPPORTUNITIES FOR CHILDREN WITH SPECIAL EDUCATIONAL NEEDS PREPARATORY TO SCHOOL - Prudņikova, Ilga; Jankovska, Jekaterina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Modern educational process is a qualitative condition in preparation of children with special educational needs for school. Information and communication technologies incorporation in the educational process is a requirement of modern learning environment. Preparation of children with special needs for school, inclusive education and individual approach is possible with innovative methods in the educational process in preschool. On one hand, information and communication technologies are learning environment improvement factors, as well as a challenging factor for teachers affecting teachers’ professional competence development.